2006
DOI: 10.1002/lt.20657
|View full text |Cite
|
Sign up to set email alerts
|

Cystatin C as a marker of renal function immediately after liver transplantation

Abstract: To verify whether cystatin C may be of some use as a renal function marker immediately after orthotopic liver transplantation (OLT), we compared serum cystatin C (S Cyst ), serum creatinine (S cr ), and creatinine clearance (C cr ) levels with the glomerular filtration rate (GFR). On postoperative days 1, 3, 5, and 7, S Cyst and S cr was measured in simultaneously drawn blood samples, whereas C cr was calculated using a complete 24-hour urine collection. The GFR was determined on the same days by means of iohe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 24 publications
0
37
0
Order By: Relevance
“…The Hoek et al (119) and Larsson et al (120) equations perform at least as well as the MDRD equation in these populations (131). CysC appears to be a better predictor of acute renal failure after liver transplantation (204), including children (146), and to provide better follow-up for moderate changes in renal function (152).…”
Section: Cysc and Hepatocellular Failurementioning
confidence: 94%
See 1 more Smart Citation
“…The Hoek et al (119) and Larsson et al (120) equations perform at least as well as the MDRD equation in these populations (131). CysC appears to be a better predictor of acute renal failure after liver transplantation (204), including children (146), and to provide better follow-up for moderate changes in renal function (152).…”
Section: Cysc and Hepatocellular Failurementioning
confidence: 94%
“…In this context, several groups have tried to establish whether CysC could be a more sensitive marker than creatinine for the early detection of deterioration in GFR in renal transplant patients. Results are inconsistent, some authors finding CysC to offer improved sensitivity (90,91,122,152), whereas according to others the diagnostic performance (assessed by ROC curve methods) does not differ significantly between the two markers, in particular for the critical GFR threshold of 60 mL/min (52, 92, 153). …”
Section: Utility Of Cysc In Transplantationmentioning
confidence: 98%
“…Of note, serum cystatin C concentration increases already with mildly reduced GFR of 70 to 90 mL/min [39,[47][48][49], i.e., in the "creatinine-blind range". Furthermore, recent longitudinal studies have shown that cystatin C concentrations rise earlier in acute kidney injury on intensive care unit, after liver transplantation, cardiac surgery, cisplatin chemotherapy and coronary angiography [51][52][53][54][55][56], following uninephrectomy [57], and in progressive diabetic nephropathy [32]. First studies have demonstrated that serum β-trace protein may be as valuable as cystatin C to detect mildly reduced GFR [58][59][60].…”
Section: Cystatin Cmentioning
confidence: 99%
“…Furthermore, the measurement of S Cr using the Jaffe method can be artificially lowered due to hyperbilirubinemia [13], or raised by cephalosporins [14] leading to variability in MELD scores [15]. Serum cystatin C has been suggested as a sensitive marker of renal function [16-22]; however, recent studies have shown that like S Cr , cystatin C is affected by age, gender, muscle mass and liver disease and overestimates renal function in patients with cirrhosis [17,23]. …”
Section: Resultsmentioning
confidence: 99%